Human Walking Centre of Mass Trajectory and Dual-Degree-of-Freedom Power Suspension Backpack System - Shi, Qiwei; Qi, Yuming; Deng, Sanpeng (International Journal of Public Health and Medical Research, 2024)
The human body generates a sophisticated three-dimensional complex motion of the centre of mass when walking, with the majority of this vibration occurring in the vertical and coronal axes. This paper presents an analysis of the human walking motion, accompanied by the establishment of an equivalent model of the human walking COM motion. This law is integrated into the coronal plane to generate the Lissajous curve expression of the human walking COM motion trajectory. Finally, the reliability of the results was verified by comparing the COM motion equivalent model with several sets of walking experimental data. The model is capable of accurately predicting and analysing the walking amplitude and frequency of the COM at varying heights and speeds. Furthermore, a dual-degree-of-freedom power suspension backpack system has been designed based on the model, which has the potential to significantly reduce the low-frequency vibration and inertial force impacts of heavy loads on the human body’s vertical and coronal axes during load-bearing walking. This could help to alleviate the resulting mechanical injuries to the human body and reduce the additional metabolic energy consumption required to resist these impacts. The device is capable of effectively reducing the low-frequency vibration and inertial force impacts in the vertical and coronal axes of the human body when walking with a load.